2015
DOI: 10.3402/gha.v8.29003
|View full text |Cite
|
Sign up to set email alerts
|

‘You must carry your wheelchair’ – barriers to accessing healthcare in a South African rural area

Abstract: BackgroundThere is international evidence that people with disabilities face barriers when accessing primary healthcare services and that there is inadequate information about effective interventions that work to improve the lives of people with disabilities, especially in low-income and middle-income countries. Poor rural residents generally experience barriers to accessing primary healthcare, and these problems are further exacerbated for people with disabilities.ObjectiveIn this study, we explore the challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
2
9

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(106 citation statements)
references
References 36 publications
7
88
2
9
Order By: Relevance
“…14 Thus, this can potentially hamper them to attain a better health outcome. 15,16 In addition, without the appropriate wheelchair, mobility outside their homes becomes more difficult or not possible. This will lead to a poorer quality of lifepossibly related to lack of opportunities and access to social activities, education, and employment.…”
Section: Discussionmentioning
confidence: 99%
“…14 Thus, this can potentially hamper them to attain a better health outcome. 15,16 In addition, without the appropriate wheelchair, mobility outside their homes becomes more difficult or not possible. This will lead to a poorer quality of lifepossibly related to lack of opportunities and access to social activities, education, and employment.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study has reported that poor people living with disabilities in rural areas experience unique problems in accessing healthcare and there is higher prevalence of disability in the rural compared with the urban areas. 23,24 OOP expenditures for health care are a huge burden and a big challenge for the poor. This is too difficult for the rural and tribal communities to manage and cope with the high costs.…”
Section: Themementioning
confidence: 99%
“…Often the physically disabled persons may defer taking care of their health needs or preventive services because of the cost (deVries‐McClintock et al., ). The lack of health insurance and the inability to pay any associated expenses has contributed to lack of preventive services received by this population (Chevarley et al., ; Vengunst, Swartz, Mji, MacLachlan, & Mannan, ).…”
Section: Synthesis Of the Literaturementioning
confidence: 99%
“…In addition, diagnostic equipment such as mammogram machines could not accommodate wheelchair bound individuals (Pharr, 2014;Smith, 2008). Vergunst, Swartz, Mji, MacLachlan, and Mannan (2015) To study the challenges faced by persons with disabilities when accessing health care in a rural setting in South Africa Phenomonological; semistructured interviews; n = 26…”
Section: Physical Environment and System Issuesmentioning
confidence: 99%